First limnological records of highly threatened tropical high-mountain crater lakes in Ethiopia - Degefu, Fasil; Herzig, Alois; Jirsa, Franz; Schagerl, Michael (Tropical Conservation Science, 2014)
Lakes Dendi, Wonchi and Ziqualla are among the few remnants of undisturbed crater lakes in the central highlands of Ethiopia, and have never been investigated reliably owing to seclusion and inaccessibility. As the lakes offer a pristine environment in a beautiful landscape and are located in the vicinity of the capital city Addis Ababa, they are highly threatened by unsustainable tourism, shoreline and crater rim modifications, water abstraction and land grabbing. We provide a first limnological description to establish baseline data against which future environmental and biological changes can be monitored. The lakes are located above 2,800 m elevation with no surface outflow and generally show low concentrations of ions, displaying an equal distribution of readily soluble components like Na or K throughout the water column, but distinct oxygen depletion in greater depths linked to rising concentrations of Fe and Mn, which indicates subterranean springs. Based on nutrients, chlorophyll a, and water transparency, lakes Dendi and Wonchi are classified as oligotrophic and Ziqualla as oligo-mesotrophic. The phytoplankton community is dominated by coccal green algae, desmids and dinoflagellates in lakes Dendi and Wonchi, typical for unpolluted dilute waterbodies; whereas chlorococcales, in particular Botryococcus braunii and benthic diatoms, prevail in Ziqualla. The zooplankton fauna is depauperate, comprising a total of 11 rotifer taxa and 13 crustaceans. Copepods were the most abundant group and contributed over 60% to the total zooplankton abundance in all three lakes, followed by rotifers and cladocerans. The conservation significance of these lakes lies predominantly in their representation of dilute, nutrient–poor highland lake systems that support diverse biota assemblages like desmids and daphnids, which are highly sensitive to eutrophication.